An overview of systematic reviews found suboptimal reporting and methodological limitations of mediation studies investigating causal mechanisms - Cashin, A; Lee, H; Lamb, S; Hopewell, S; Mansell, G; Williams, C; Kamper, S; Henschke, N; McAuley, J (Elsevier, 2019)
Objectives: The objective of this study was to investigate whether systematic reviews of mediation studies identify limitations in reporting quality and methodological conduct.